2013
DOI: 10.1371/journal.pone.0073346
|View full text |Cite
|
Sign up to set email alerts
|

Xanthomonas oryzae pv. oryzae Type III Effector XopN Targets OsVOZ2 and a Putative Thiamine Synthase as a Virulence Factor in Rice

Abstract: Xanthomonas oryzae pv. oryzae (Xoo) is spread systemically through the xylem tissue and causes bacterial blight in rice. We evaluated the roles of Xanthomonas outer proteins (Xop) in the Xoo strain KXO85 in a Japonica-type rice cultivar, Dongjin. Five xop gene knockout mutants (xopQ KXO85, xopX KXO85, xopP1 KXO85, xopP2 KXO85, and xopN KXO85) were generated by EZ-Tn5 mutagenesis, and their virulence was assessed in 3-month-old rice leaves. Among these mutants, the xopN KXO85 mutant appeared to be less vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 53 publications
(60 reference statements)
1
27
0
Order By: Relevance
“…Although the genome sequence of Xcc MAFF106712 is not available so far, it harbours at least XopN, XopK, XopQ, XopZ and XopR (Akimoto‐Tomiyama et al ., ). Single mutations of XopN, XopQ, XopZ (Cheong et al ., ; Gupta et al ., ; Song and Yang, ) and XopR (Akimoto‐Tomiyama et al ., ) have already been reported to affect virulence. Further analysis is needed to determine the T3E(s) involving PP2C expression and those T3Es with the potential to attenuate photosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Although the genome sequence of Xcc MAFF106712 is not available so far, it harbours at least XopN, XopK, XopQ, XopZ and XopR (Akimoto‐Tomiyama et al ., ). Single mutations of XopN, XopQ, XopZ (Cheong et al ., ; Gupta et al ., ; Song and Yang, ) and XopR (Akimoto‐Tomiyama et al ., ) have already been reported to affect virulence. Further analysis is needed to determine the T3E(s) involving PP2C expression and those T3Es with the potential to attenuate photosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…XopN has been reported to be an important virulence factor in other Xanthomonas spp. (Cheong et al, 2013;Jiang et al, 2008). It interacts with a 14-3-3 (TFT1) protein and with the Tomato Atypical Receptor-Like Kinase 1 (TARK1) in S. lycopersicum (Kim et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Work in our laboratory has already shown that Xvm expressed HrpF (an indispensible gene for establishment of the type three secretion system) during infection of banana. Pathogen effectors are known to variously suppress host defence mechanisms [23] [24]. Repression of MbNBS below basal levels in the early hours following inoculation with Xvm therefore suggests that this pathogen causes its down regulation to evade detection (of its effectors).…”
Section: Discussionmentioning
confidence: 99%